Clave del relato histórico de Alfredo Pareja Diezcanseco: herencia colonial, Revolución liberal y mestizaje - Bustos, Guillermo (2008)
The author analyzes Pareja's perspective on the problems and achievements of the country until the 1950's; he argues that they are republican secular, socialist, modernizing and guayaquilian. Sorne of Pareja's appreciations are based in the context of lack of historiographic knowledge in Ecuador during those years. His perspective on the conquest has elements of a Hispanic vision of how history unfolds, which seeks to reconcile itself with the search for a modernity not yet attained yet passionately desired. Regarding the era of Independence, liberty wasn't gained in 1822, but only in 1895, with the Liberal Revolution, which brought the modernization of the State; in which the mestizo will playa central role. Finally, Pareja attributes mestizization to the possibility of making the nation part of a more civilized dynamic, with up-to-date notions of democracy and progress.